2011
DOI: 10.1097/sih.0b013e31822b1307
|View full text |Cite
|
Sign up to set email alerts
|

Deliberate Practice Using Simulation Improves Neonatal Resuscitation Performance

Abstract: Our results suggest that DP using simulation is associated with improvements in NRP performance and support the use of DP using simulation in NRP training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 22 publications
(28 reference statements)
2
80
0
Order By: Relevance
“…1,2,4 Repetitive practice as provided by simulation has been shown to increase competence in the performance of many clinical procedures, including endoscopy, 5 thoracentesis, 6 advanced cardiac life support, 7 cardiac auscultation, 8 central line placement, 9 lumbar puncture, 10 and neonatal resuscitation skills. 11 Repeated exposure to simulated cases has been shown to improve performance, but repeating case scenarios decreases the learner's overall breadth of exposure. Repeated practice may be exceptionally useful in fields where a few scenarios make up the majority of emergency situations.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,4 Repetitive practice as provided by simulation has been shown to increase competence in the performance of many clinical procedures, including endoscopy, 5 thoracentesis, 6 advanced cardiac life support, 7 cardiac auscultation, 8 central line placement, 9 lumbar puncture, 10 and neonatal resuscitation skills. 11 Repeated exposure to simulated cases has been shown to improve performance, but repeating case scenarios decreases the learner's overall breadth of exposure. Repeated practice may be exceptionally useful in fields where a few scenarios make up the majority of emergency situations.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown the benefits of training in neonatal resuscitation for improved perinatal outcomes (Draycott et al, 2006;Jukkala and Henly, 2007;Lee et al, 2011;Singh et al, 2006). Simulation in clinical education imitates the management of real life situations as a method of training and has been shown to be an effective method of teaching within neonatal resuscitation courses (Campbell et al, 2009;Cates, 2011;Halamek et al, 2000;Hamalek, 2008;Rovamo et al, 2013;Sawyer et al, 2011;Yaegar and Arafeh, 2008) and there is growing evidence that simulation in midwifery education should be the standard (Cooper et al, 2011;Lathrop et al, 2007). However, there is little evidence examining the effect of neonatal resuscitation training for midwifery students, either in their confidence or performance at neonatal resuscitation or when routinely receiving the newborn at birth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the findings of this study and related simulation literature, the next step should be to teach PoCUS choreography in HFS. Existing evidence of improved team performance 20,21 and resuscitation 22,23 supports the use of simulation interventions for the integration of resuscitative PoCUS.…”
Section: Secondary Outcomesmentioning
confidence: 99%